Evaluasi Lingkungan Pengendalian dengan Kerangka Pengendalian Internal COSO di KPP Pratama Jakarta Pesanggrahan - Sekar Puspita Ayu Setiyaviani; Lufti Julian (Owner : Riset dan Jurnal Akuntansi, 2023)
The control environment is crucial for establishing a reliable internal control system to prevent corporate fraud at the Jakarta Pesanggrahan Tax Office. It collects state revenue and accesses sensitive taxpayer information, including personal identity and financial data, making it susceptible to fraud risks. This study evaluates the control environment components of the Jakarta Pesanggrahan Tax Office using the 2013 edition of the COSO Internal Control Framework. The study used qualitative descriptive and case study methods. The population of this tax office consists of 93 employees. Primary data was collected through semi-structured interviews with 20 informants from various sections. Secondary data was collected through online sources, regulations, reports, and a literature review. The novelty in this study is that researchers used thematic analysis to produce 37 themes used as indicators in the suitability assessment of control environment components. The research results show that Jakarta Pesanggrahan Tax Office has 31 out of 37 indicators. In the "The organization demonstrates a commitment to integrity and ethical values" component, there are findings of working hours violations. In the component "The board of directors demonstrates independence from management and exercises oversight of the development and performance of internal control," there are repeated findings from the Supreme Audit Agency of the Republic of Indonesia, and the structure of the Internal Compliance Unit needs to operate independently. In the component "Management establishes, with board oversight, structures, reporting lines, and appropriate authorities and responsibilities in the pursuit of objectives," there are differences in perceptions between personnel of the Compliance Committee and inconsistencies in work positions. In the "The organization demonstrates a commitment to attract, develop, and retain competent individuals in alignment with objectives," the Jakarta Pesanggrahan Tax Office has fulfilled all indicators. Finally, in the component "The organization holds individuals accountable for their internal control responsibilities in the pursuit of objectives," the finding is the form of quality inequality resulting from employee performance ratings. Overall, the study aims to contribute to developing knowledge about the control environment in the tax office.